2019
DOI: 10.18697/ajfand.84.blfb1006
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Variability and New Sources of Resistance to Angular Leaf Spot Among Bean Landraces in Uganda

Abstract: Angular leaf spot (ALS), a fungal disease caused by Pseudocercospora griseola, has a significant impact on bean productivity in Africa, causing up to 80% yield losses. Efforts to breed for ALS resistance are challenged by continuously evolving pathogen races that differ by location. Released bean varieties in Uganda are susceptible to ALS; the few exotic sources of resistance available are not well adapted to local environmental conditions. To overcome these challenges, a study was conducted to understand path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…The exception was revealed by the STRUCTURE analysis of the breeder-selected and household collection samples, which identified a fourth distinct population, based on the Evanno et al (2005) test, indicating more complex population structure in household seed stocks relative to the global germplasm collection (Figure 5). Control genotypes, visual inspection of seed morphological traits, and prior information obtained from previous molecular analyses (Gepts, 1988; Ddamulira et al, 2014; Okii et al, 2014), provided additional empirical support for characterization of the K = 4 populations. The fourth population was primarily composed of Andean seed samples that household members consistently referred to as “Seed Engufu” (translated from the local Bantu language, Runyoro or Nyoro, as “short seed”).…”
Section: Resultsmentioning
confidence: 89%
“…The exception was revealed by the STRUCTURE analysis of the breeder-selected and household collection samples, which identified a fourth distinct population, based on the Evanno et al (2005) test, indicating more complex population structure in household seed stocks relative to the global germplasm collection (Figure 5). Control genotypes, visual inspection of seed morphological traits, and prior information obtained from previous molecular analyses (Gepts, 1988; Ddamulira et al, 2014; Okii et al, 2014), provided additional empirical support for characterization of the K = 4 populations. The fourth population was primarily composed of Andean seed samples that household members consistently referred to as “Seed Engufu” (translated from the local Bantu language, Runyoro or Nyoro, as “short seed”).…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, progress in breeding for ALS resistance has been slow, mainly because of the high diversity of ALS pathogen races found in East Africa (Wagara et al, 2011;Ddamulira et al, 2014b;Leitich, 2016;Kijana et al, 2017). Research on ALS in East Africa has focused on the identification and genetic characterization of new sources of resistance in local landraces and released varieties (Ng'ayu-Wanjau, 2013;Ddamulira et al, 2014a;Leitich, 2016;Kijana et al, 2017). In these studies, Mexico 54 was found to be resistant to most races of P. griseola, and this cultivar is the most common source of ALS resistance in breeding in Uganda and East Africa (Namayanja et al, 2006;Chilagane et al, 2013;Ng'ayu-Wanjau, 2013;Ddamulira et al, 2015;Miller et al, 2018).…”
Section: Breeding For Angular Leaf Spot Resistance In East Africamentioning
confidence: 99%
“…The major diseases constraining common bean productivity in Eastern and Central Africa include angular leaf spot (ALS) caused by Pseudocercospora griseola (Sacc.) (Ddamulira et al, 2014;Leitich et al, 2016) and anthracnose (Colletotrichum lindemuthianum (Sacc. and Magn.…”
Section: Marker-assisted Gamete Selection For Multiple Disease Resistmentioning
confidence: 99%
“…First, is the occurrence of new races and strains of disease pathogens, such as ALS, anthracnose, root rots, and BCMV (Leitich et al, 2016;Mwaipopo et al, 2017). In addition, there is insufficient identification and deployment of new sources of resistance to the emerging pathotypes (Ddamulira et al, 2014;Mukankusi et al, 2018), as well as a narrow genetic base within existing breeding populations, especially for grain yield potential and disease resistance. This threatens progress towards improvement for these traits (Kimani et al, 2005b;Asfaw et al, 2009).…”
Section: Marker-assisted Gamete Selection For Multiple Disease Resistmentioning
confidence: 99%